Geopolitik dan geostrategi di Indonesia: Geopolitik dan geostrategi Indonesia dalam memperkuat ketahanan nasional dan keutuhan NKRI - hayati, amal (Maliki Interdisciplinary Journal, 2026)
Indonesian geopolitics relates to the Indonesian people’s perspective on territory, geographical position, and national interests as embodied through the Indonesian Archipelago Insight. Meanwhile, Indonesian geostrategy relates to national strategies in maintaining national resilience, unity, and sovereignty. This study aims to explain the importance of understanding geopolitics and geostrategy for citizens in facing global challenges, such as regional conflicts, threats of disintegration, competition for natural resources, and technological developments. This article uses a literature review method by analyzing various basic concepts of the Indonesian Archipelago Insight and Natonal Resilience. The results of the discussion indicate that geopolitics and geostrategy have a significant role in strengthening nationalism, maintaining the integrity of the Unitary State of the Republic og Indonesia (NKRI), and forming citizens who are aware of Indonesia’s strategic position.